2017
DOI: 10.18178/joams.5.5.373-379
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic Tourist Profile and Destination Image in Online Environment

Abstract: This paper discusses the impact of tourist's sociodemographic characteristics on destination image formation process in the online environment specifically on the web. The goal is to analyse the influence of personal factors of tourists in different destination image components by inducing stimuli such as multimedia and information mediated by the web. Literature review on destination image in digital age has been done to examine the existing measurements on image formation and the advances in online environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Many authors have so far demonstrated the influence of sociodemographic characteristics (gender, age, education, social status, marital status, occupation, income) on image perceptions [30,54,55,[70][71][72][73][74]. Therefore, it is also believed that certain sociodemographic characteristics of tourists determine their destination image perception: Hypothesis 3b (H3b).…”
Section: Destination Imagementioning
confidence: 99%
“…Many authors have so far demonstrated the influence of sociodemographic characteristics (gender, age, education, social status, marital status, occupation, income) on image perceptions [30,54,55,[70][71][72][73][74]. Therefore, it is also believed that certain sociodemographic characteristics of tourists determine their destination image perception: Hypothesis 3b (H3b).…”
Section: Destination Imagementioning
confidence: 99%
“…The travel photos allow to transfer affective feelings to the tourists, and the study of the extent to which the images published in the websites influence the tourists is of extreme importance (Gao & Bai, 2014). Images influence the purchase decision of the tourist, both at the destination level and the final decision level (Rafael & Almeida, 2017) and photographic content, in general, can be more effective to transmit emotional attributes (Mak, 2017).…”
Section: Photographsmentioning
confidence: 99%
“…Many scientists and practitioners have been studying the factors that influence the development of both the domestic and global tourism industry. Recent publications are: (Nemets, Sehida, and Moshtakova, 2009;Maklashina, 2012;Rafael, and Almeida, 2017;Sirik, 2016;Slabbert and Du Plessis, 2011) and others. Each of the above have their own view concerning the problem of analysing the factors for the development of the tourism industry: SWOT analysis of the activity in the tourism industry in Ukraine (Sirik, 2016, p. 158); diagnostics of factors influencing the process of promoting tourist destination in the virtual environment (Rafael and Almeida, 2017, pp.…”
Section: Stating the Problemmentioning
confidence: 99%